ADAPTACJA ZABYTKÓW ARCHITEKTURY W GDAŃSKU. ZARYS PROBLEMATYKI W ŚWIETLE OBOWIĄZKÓW ORGANÓW OCHRONY ZABYTKÓW - Karolina Szczepanowska (Ochrona Dziedzictwa Kulturowego)
This article discusses the issue of adaptation of immovable historic monument and sites in light of the legal requirements and from the point of view of heritage protection authorities being one of the participants of the adaptation process. The initial aim is to define the concept of monument adaptation and delineate the conditions in which such a process occurs. The article describes a series of initial actions taken prior to the actual preservation and restoration works – as part of the adaptation process. These works include e.g. detailed research on a historic monument or site, including historical (historical-preservation studies), preservation, architecture, and in many cases also archaeological research. The aim of these activities is to acquire a fullest possible picture of the monument. The results of this research then constitute a basis for preparation of project documentation of the intended works. The article underlines importance of assigning an appropriate purpose to the asset undergoing the process of adaptation, which should be merged with a monument or site, i.e. respect all of its historical values and ensure the optimal utility of the asset, avoiding a series of potential negative consequences. The paper then discusses the applicable legal framework concerning protection of immovable monuments and competences of monument protection authorities resulting from the said framework. The paper’s conclusion postulates that the activities of all personnel working on historic monuments and sites should be guided by their inner conviction that monuments need to be looked after and that they have a social duty to maintain them for the sake of future generations. This duty is actually applicable to all citizens, just as the cultural heritage is the primary building block of the nation’s historical identity.